1961
DOI: 10.1071/zo9610061
|View full text |Cite
|
Sign up to set email alerts
|

The Haematozoa of Australian Reptiles.

Abstract: Trypanosomes are known from tortoises, a gecko, and skinks, Trypanosoma phylluri from Phyllurus platurus, and T. egerniae from Egernia striolata and E. cunninghami being new. There is an old record of a trypanosome in a snake, but the organism has not been rediscovered. Haemogregarines are common in all groups. Names had already been given to 2 from tortoises (one of which is regarded as a synonym), 4 from lizards, and 10 from snakes in Australia. Three species described from snakes in Asia have been added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1
4

Year Published

1979
1979
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 13 publications
1
53
1
4
Order By: Relevance
“…has been previously described from freshwater turtles in Australia, namely T. chelodinae from C. longicollis, Emydura kreftii, E. macquarii, E. latisternum and E. dentata (cf. Mackerras, 1961). Many others have been described from chelonian hosts elsewhere in the world (Woo, 1969;Molyneux, 1977).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…has been previously described from freshwater turtles in Australia, namely T. chelodinae from C. longicollis, Emydura kreftii, E. macquarii, E. latisternum and E. dentata (cf. Mackerras, 1961). Many others have been described from chelonian hosts elsewhere in the world (Woo, 1969;Molyneux, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Infections seemed to be heavier during the winter which is when turtles hibernate, and they were heavier in older turtles suggesting they accumulate with age. Mackerras (1961) previously observed that turtles tend to develop an ongoing tolerance to these parasites rather than developing immune responses to them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1e). Following descriptions provided by Mackerras (1961) of the seven Hemogregarina species found in Australian Boidae (O'Donoghue and Adlard, 2000), the species in this study appears to be Hemogregarina moreliea. Samples were categorized according to the presence or absence of the hemoparasites in smears.…”
Section: Hematology Analysismentioning
confidence: 51%